Variasi Bahasa Mahasiswa dalam Pembelajaran Bahasa Inggris di Universitas Muhammadiyah Bone Penidikan Bahasa Inggris Semester V: Penelitian - Rhegita Egidia; Lyra Virna; A. Nurul Hidayah; Fadilla Ramadany (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe the language variations used by fifth-semester students of the English Education Study Program at Universitas Muhammadiyah Bone in the context of English as a Foreign Language (EFL) learning. The focus of the research includes the types of language variations that emerge, the contexts in which they occur, and the social and linguistic factors that influence these variations. The study employs a descriptive qualitative method, with data collected through classroom observations, recorded conversations, and informal interviews. The findings reveal that students actively use code switching, code mixing, and interlanguage as communicative strategies to explain complex concepts, adjust to interlocutors, and maintain the flow of interaction. The results also indicate that social context greatly influences language choice: students are more flexible and frequently mix languages in informal interactions, whereas English is more dominantly used in formal academic settings. Factors influencing language variation include limited vocabulary, socio-cultural identity, the need for clarification, and classroom interaction dynamics. This study concludes that language variation is an essential part of the learning process and can be utilized as a pedagogical strategy to enhance students’ comprehension.